Exploring the vulnerability of practice-like activities: An ethnographic perspective - Bolade-Ogunfodun, Yemisi; Sinnicks, Matthew; Akrivou, Kleio; Scalzo, Germán (Frontiers in Sociology, 2022)
ABSTRACT: This paper offers an ethnographic case study of a UK-based engineering company in the aftermath of its acquisition, focusing in particular on its R&D unit. The Lab struggled to maintain its practice-based work in an institutional environment that emphasised the pursuit of external goods. We use this case to develop two arguments. Firstly, we illustrate the concept of ‘practice-like’ activities and explore their vulnerability to institutional domination. Secondly, in light of the style of management on display after the takeover, we offer further support to MacIntyre’s critique of management. Finally, based on the empirical data we reflect on the importance of organisational culture, as well as friendship and the achievement of a common good in business organisations for these kinds of activities.